Fabrication and characterization of 4H-SiC bipolar junction transistor with double base epilayer - 张倩 张玉明 元磊 张义门 汤晓燕 宋庆文 (Chinese physics B, 2012)
In this paper we report on a novel structure of a 4H-SiC bipolar junction transistor with a double base epilayer that is continuously grown. The measured dc common-emitter current gain is 16.8 at Ic = 28.6 mA （Jc = 183.4 A/cm2）, and it increases with the collector current density increasing. The specific on-state resistance （Rsp-on） is 32.3 mΩ.cm2 and the open-base breakdown voltage reaches 410 V. The emitter N-type specific contact resistance and N＋ emitter layer sheet resistance are 1.7× 10-3 Ω.cm2 and 150 Ω/□, respectively.